Impact of Corporate Social Responsibility on Microfinance Banks’ Performance in Ogbomoso, Oyo State, Nigeria. - Oni, Kehinde; Aremu, Mukaila Ayanda; Ogunniran, Taiwo (Technium Social Sciences Journal, 2022)
Over the years, few organisations are gradually coming to terms with the pertinence and essentiality of the strategic and pregnable tool of Corporate Social Responsibility (CSR) in the attainment of organisational goals. While some are facing various issues while adopting CSR practices, others are yet to know which CSR activities is best to adopt based on their physical needs. Therefore, this study empirically investigates the role of CSR in the attainment of organisational performance in Ogbomoso Microfinance Bank (MFB). Four research objectives on the relationship between CSR and key important aspect of MFB in Ogbomoso were deployed to 80 employees across Ogbomoso MFB using survey research design. Different analysis such as descriptive statistics, Pearson’s Correlation and regression analysis and T-square with the aid of SPSS were used for the analysis of this survey. The findings revealed that there is a significant correlation between CSR and effectiveness of organisational performance as well as employees and environments. The analysis of the CSR and organisation performance recorded a F-statistics value of 3.648 and p-value of 0.005<0.05. The study also found out that the participation of MFBs in CSR activities is somewhat low based on the statistical analysis which recorded a T-value of 0.263 < 1.96 with significance ratio of 0.793 > 0.05 which indicates that each of the microfinance bank in Ogbomosho spend less than 10% of their profit on CSR activities. Therefore, the study recommends that Ogbomoso MFB should proactively involve in CSR for a significant contribution to productivity and stability.